2002
DOI: 10.1063/1.1506420
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and magnetic properties of Co/Pd multilayered thin films with C or Si seedlayer

Abstract: Microstructure and magnetic properties of sputter deposited Co/Pd multilayered perpendicular magnetization films with amorphous C or Si seedlayer were investigated. The angstrom scale surface roughness of the seedlayer causes fine crystal grains to form in the Co/Pd multilayer and to decrease the extent of intergranular exchange coupling, while it obstructs the formation of a regular interface between Co and Pd layers. The Si seedlayer, which exhibits a surface roughness lower than the C seedlayer, yields Co/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…[9][10][11]13 Onoue et al reported that an increase in the thickness of amorphous C or Si seedlayer greatly enhanced the perpendicular coercivity (H c ) and the nucleation field of reversed magnetic domains. [20][21][22][23][24] They also reported that the seedlayer reduces the intergranular exchange coupling and magnetic domain size of the media, resulting in an improvement of signal-to-noise ratio in their read-write ͑R/W͒ experiment, and that an amorphous C or Si seedlayer is useful for the ͓Co/Pd͔ 20 media. The increase in the thickness of C or Si seedlayer leads to improvements in recording performance, but it accompanies a decrease in K u .…”
Section: Introductionmentioning
confidence: 93%
“…[9][10][11]13 Onoue et al reported that an increase in the thickness of amorphous C or Si seedlayer greatly enhanced the perpendicular coercivity (H c ) and the nucleation field of reversed magnetic domains. [20][21][22][23][24] They also reported that the seedlayer reduces the intergranular exchange coupling and magnetic domain size of the media, resulting in an improvement of signal-to-noise ratio in their read-write ͑R/W͒ experiment, and that an amorphous C or Si seedlayer is useful for the ͓Co/Pd͔ 20 media. The increase in the thickness of C or Si seedlayer leads to improvements in recording performance, but it accompanies a decrease in K u .…”
Section: Introductionmentioning
confidence: 93%
“…Ferromagnetic nanowires synthesized by various methods, [1][2][3] exhibit unique and tuneable magnetic properties due to the inherent shape anisotropy and the small wire dimensions. These nanomaterials exhibit unique magnetic properties for further application, such as high squareness and high coercivity.…”
Section: Introductionmentioning
confidence: 99%
“…Ferromagnetic nanowires synthesized by various methods [1][2][3], exhibit unique and tuneable magnetic properties due to the inherent shape anisotropy and the small wire dimensions. These nanomaterials exhibit unique magnetic properties for further application, such as high squareness and high coercivity [4].…”
Section: Introductionmentioning
confidence: 99%